2006
DOI: 10.1088/0957-4484/17/23/023
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles with enhanced γ-Fe2O3to α-Fe2O3phase transition temperature

Abstract: We report a simple method for producing magnetic nanoparticles with enhanced maghemite (γ-Fe2O3) to haematite (α-Fe2O3) phase transition temperature. By controlling the properties of the solvent media, we have been able to tune the particle size from 2.3 to 6.5 nm. Nanoparticles with higher transition temperatures have been achieved by using NaOH as an alkali during the co-precipitation. The maghemite to haematite phase transition was complete at a temperature below 600 °C for nanoparticles prepared using amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 48 publications
3
56
0
2
Order By: Relevance
“…3 shows the XRD pattern of sintered powders at 400-900 1C. The XRD pattern of powder sintered at 400 1C is composed of strong b-Bi 2 O 3 peaks [16] with weak g-Fe 2 O 3 peaks [17] but the Y 2 O 3 phase cannot be seen. This suggests that the decomposition of bismuth and iron carboxylate occur at lower temperature than yttrium carboxylate.…”
Section: Powder Analysismentioning
confidence: 99%
“…3 shows the XRD pattern of sintered powders at 400-900 1C. The XRD pattern of powder sintered at 400 1C is composed of strong b-Bi 2 O 3 peaks [16] with weak g-Fe 2 O 3 peaks [17] but the Y 2 O 3 phase cannot be seen. This suggests that the decomposition of bismuth and iron carboxylate occur at lower temperature than yttrium carboxylate.…”
Section: Powder Analysismentioning
confidence: 99%
“…The forth term in (1) represents the influence of the external magnetic field, being h andĥ magnetic field and its direction respectively. For the simulation, three types of bond are considered: Mn 3+e g -OMn 3+e g , Mn 3+e g -O-Mn 4+d 3 and Mn 3+e g -O-Mn 4+d 3 with exchange parameters (J ij ) of J 1 = 4.65 eV, J 2 = 7.7 meV and J 3 = 1.4 meV respectively, according to the study reported by J.C. Riaño-Rojas et al [16]. On the other hand, in this case, single-spin Metropolis Monte Carlo algorithm was used, for obtaining equilibrium thermodynamic properties.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Magnetic nanoparticles have attracted a great deal of attention since they lead to many size dependent, electrical, magnetic, chemical, and optical properties [1][2][3]. One of the most studied magnetic materials employed in nanotechnology are doped manganites.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, the transformation of Fe 3 O 4 into c-Fe 2 O 3 and a-Fe 2 O 3 is very common; it occurs in the oxidization of Fe 3 O 4 . [27,28] On the other hand, a-Fe 2 O 3 is reduced to c-Fe 2 O 3 , and Fe 3 O 4 when a reducing agent such as hydrogen gas is used during heat treatment [29]. In our system, during the sample annealing process, the reduction process occurs without requiring any additional reducing agent, thus c-Fe 2 O 3 , Fe 3 O 4 , and Fe can be selectively obtained from as-prepared a-Fe 2 O 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%